Mechanism and Potential Therapeutic Strategies Based on PRMT5 in Chemotherapy-Induced Drug Resistance in Non-Small Cell Lung Cancer - Zhang, Zheng; Liu, Yi (International Journal of Public Health and Medical Research, 2024)
As a malignant tumor with high morbidity and mortality in the world, the treatment of non-small cell lung cancer is still facing great challenges. Although new breakthroughs have been made in recent years and great progress has been made in chemotherapy and targeted therapy, the five-year survival rate of most NSCLC patients is still at a low level. The emergence of drug resistance is one of the important factors affecting the therapeutic effect and survival rate of patients. PRMT5 (protein arginine methyltransferase 5), as a type II arginine methyltransferase, plays an important role in cancer cell proliferation, differentiation, apoptosis and tumorigenesis. At present, people pay more and more attention to the research on the mechanism of PRMT5 in tumor drug resistance. In this review, we summarize the mechanism of PRMT5 in chemotherapy resistance of non-small cell lung cancer and discuss potential strategies to avoid or overcome chemotherapy resistance.